Shining Through the Hierarchy: Rachel Kim’s Psychological Journey in Shine by Jessica Jung Through Maslow’s Lens - Sawintri, Anita Beli; Wajiran, Wajiran (LPPM Universitas Bumigora Mataram, 2025)
This study explores Rachel Kim’s psychological development in Shine by Jessica Jung through the lens of Maslow’s Hierarchy of Needs. Rachel’s journey as a K-pop trainee illustrates the progression through Maslow’s five levels—physiological, safety, love and belongingness, esteem, and self-actualization. The novel highlights how Rachel and her family struggle with financial stability, addressing her psychological and safety needs. As she navigates friendships, family expectations, and industry challenges, Rachel’s love and belongingness needs come into focus. Her self-esteem is tested by public scrutiny and personal setbacks, but is ultimately restored through support from loved ones. The culmination of her journey is self-actualization, as she embraces her talent and achieves her dream of debuting as a K-pop idol. Through Rachel’s character arc, Shine reflects the universal nature of human motivation, demonstrating how ambition, resilience, and emotional fulfillment shape an individual’s growth. This analysis provides a deeper understanding of the novel’s themes, emphasizing the interplay between personal aspirations and psychological development in high-pressure environments.